2014
DOI: 10.4322/tmm.2014.028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pitting Corrosion on an Inconel 718 Alloy Submitted to Aging Heat Treatment

Abstract: Inconel 718 is one of the most important superalloys, and it is mainly used in the aerospace field on account of its high mechanical strength, good resistance to fatigue and creep, good corrosion resistance and ability to operate continuously at elevated temperatures. In this work the resistance to pitting corrosion of a superalloy, Inconel 718, is analyzed before and after double aging heat treatment. The used heat treatment increases the creep resistance of the alloy, which usually is used up to 0.6 T m . Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Pedron and Pineau [25] performed fatigue crack growth tests on alloy 718 at 650°C under air Page 15 of 44 A c c e p t e d M a n u s c r i p t 15 and vacuum environments to investigate the influence of microstructure and environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pedron and Pineau [25] performed fatigue crack growth tests on alloy 718 at 650°C under air Page 15 of 44 A c c e p t e d M a n u s c r i p t 15 and vacuum environments to investigate the influence of microstructure and environment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it was shown that the i corr of Alloy718-TSA is higher than the one of Alloy 718-SA, confirming the lower corrosion resistance due to the bigger grain size and formation of new  phases. It should be pointed out that Alloy 718-OSA shows lower i corr values than Alloy718-SA, which might be ascribed to the formation of the nano-size γ′/ γ″ precipitates [15]. respectively, which shows the same trend of corrosion resistance of three alloy 718 specimens in 3.5 wt.% NaCl solution.…”
Section: Potentiodynamic Polarizationmentioning
confidence: 95%
See 2 more Smart Citations
“…IN-718 is a precipitation-hardenable austenitic Ni–Cr–Fe superalloy (Figure 1) with excellent oxidation- [1] and corrosion resistance [2]. It combines high strength and good ductility up to temperatures of K ( ) and it possesses good phase stability, weldability, castability, and machinability.…”
Section: Introductionmentioning
confidence: 99%